A SCIENTIFIC PUBLICATIONS IN EDUCATION: A “SCOURGE” FOR ACADEMICS - OKTAVIANI ADHI SUCIPTANINGSIH; KHUSNUL KHOTIMAH; MARDHATILLAH; MUHIBUDDIN FADHLI (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Scientific publication is an academic activity that must be carried out. This article aims to analyze scientific publications in education: the “scourge” for academics. Several academics consisting of 10 lecturers, 10 teachers, and 10 students were interviewed to obtain valid data. Apart from that, observations and analysis of several documents were carried out to support valid data. The results show that academics have difficulty carrying out scientific publications due to limited knowledge and information regarding how to write scientific articles by journal standards, difficulty finding credible journals, difficulty identifying journals that suit the topic and scope of the article, language limitations, high publication costs, and intensity. Rejection from the journal editor. Based on the treatment carried out, namely through training on the effective scientific publication strategy "MeRePeCeKoRe", there was an increase in the knowledge and ability of academics to conduct scientific publications by 80%. Academics need practice and a habit of writing articles to improve their skills in scientific publications.